DESEMINASI HASIL PENELITIAN INTERAKSI SOSIAL DAN SIKAP MULTIKULTURALISME MAHASISWA UNIVERSITAS X DI JAKARTA - Ninawati (Jurnal Serina Abdimas, 2023)
Building awareness of multiculturalism in a nation-state like Indonesia is not an easy endeavor, especially with the awareness that Indonesia is a country characterized by a heterogeneous society, a multicultural and multi-ethnic country. Multiculturalism not only requires living together based on the principle of diversity in diversity which is full of tolerance and harmony, but also understanding and respect for inter-cultural, inter-religious, inter-ethnic groups in fostering a societal order full of peace, tranquility and love (Shofa, 2016) . Various ways and steps are used so that this attitude of multiculturalism can grow in Indonesian society. One way is through social interaction by individuals. The process of creating a multicultural society requires a willingness to take action from the government, especially in the field of education by emphatically conveying multicultural aspects. Multicultural problems in Indonesian society need awareness to understand them. In a multicultural and multiethnic society maintaining relationships and interactions is very much needed in order to get a safe society. For this reason, maintaining good relations in order to create a safe atmosphere requires interaction that exists between its citizens. Through this dissemination activity it is introduced how social interaction occurs in order to create a good multicultural attitude among students. By holding dissemination through webinars, it is hoped - a little or a lot - to add insight or knowledge about the need for a multicultural attitude. Dissemination was carried out through an online seminar on November 30, 2022 with the topic "Indonesian Agents of Change Festival: Celebrating Diversity Through Education and Culture". This seminar apart from presenting the results of the research also featured several other speakers working in the field of cultural change. The webinar involved 177 participants from various institutions and universities. The activities ran smoothly and the time allocation was relatively appropriate. Membangun kesadaran multikulturalisme dalam sebuah negara-bangsa, seperti Indonesia bukanlah upaya yang mudah, terlebih lagi dengan kesadaran Indonesia adalah negara dengan ciri masyarakat heterogen, negara multikultural dan multi etnis. Multikulturalisme bukan saja hanya menuntut kehidupan bersama berdasarkan asas bhineka tunggal ika yang penuh toleransi, dan rukun-rukun saja tetapi juga pengertian dan penghargaan antarbudaya, antaragama, antaretnis dalam membina suatu tatanan masyarakat yang penuh dengan kedamaian, ketentraman dan cinta kasih (Shofa, 2016). Berbagai cara dan Langkah digunakan agar sikap multikulturalisme ini dapat tumbuh dalam masyarakat Indonesia. Salah satunya adalah melalui interaksi sosial yang dilakukan individu. Proses untuk mewujudkan masyarakat multikultural memerlukan kemauan tindakan dari pemerintah terutama dalam bidang Pendidikan dengan menyampaikan aspek multikultural secara tegas. Masalah multikultural pada masyarakat Indonesia perlu kesadaran untuk memahaminya. Pada masyarakat multikultural dan multietnis menjaga relasi dan interaksi amat diperlukan agar mendapatkan masyarakat yang aman. Untuk itu menjaga hubungan baik demi terciptanya suasana yang aman memerlukan interaksi yang terjalin di antara warganya.Melalui kegiatan diseminasi ini diperkenalkan bagaimana interaksi sosial yang terjadi agar tercipta sikap multikultural yang baik di kalangan mahasiswa. Dengan diselenggarakannya diseminasi melalui webinar diharapkan - sedikit atau banyak -menambah wawasan atau pengetahuan tentang perlunya sikap multikultural. Diseminasi dilakukan melalui seminar daring pada tanggal 30 November 2022 dengan topik “Festival Agen Perubahan Indonesia: Merayakan Keberagaman Melalui Pendidikan dan Kebudayaan”. Seminar ini selain menyampaikan hasil penelitian juga menampilkan beberapa narasumber lainnya yang bergerak dalam bidang perubahan kebudayaan. Pelaksanaan webinar melibatkan 177 orang peserta dari berbagai Lembaga dan perguruan tinggi. Kegiatan berjalan lancar dan alokasi waktu relatif tepat.